Adipocytes fail to maintain cellular identity during obesity due to reduced PPARγ activity and elevated TGFβ-SMAD signaling - Hyun Cheol Roh; Manju Kumari; Solaema Taleb; Danielle Tenen; Christopher Jacobs; Anna Lyubetskaya; Linus T.-Y. Tsai; Evan D. Rosen (Elsevier, 2020)
Objective: Obesity due to overnutrition causes adipose tissue dysfunction, which is a critical pathological step on the road to type 2 diabetes (T2D) and other metabolic disorders. In this study, we conducted an unbiased investigation into the fundamental molecular mechanisms by which adipocytes transition to an unhealthy state during obesity. Methods: We used nuclear tagging and translating ribosome affinity purification (NuTRAP) reporter mice crossed with Adipoq-Cre mice to determine adipocyte-specific 1) transcriptional profiles (RNA-seq), 2) promoter and enhancer activity (H3K27ac ChIP-seq), 3) and PPARγ cistrome (ChIP-seq) profiles in mice fed chow or a high-fat diet (HFD) for 10 weeks. We also assessed the impact of the PPARγ agonist rosiglitazone (Rosi) on gene expression and cellular state of adipocytes from the HFD-fed mice. We integrated these data to determine the transcription factors underlying adipocyte responses to HFD and conducted functional studies using shRNA-mediated loss-of-function approaches in 3T3-L1 adipocytes. Results: Adipocytes from the HFD-fed mice exhibited reduced expression of adipocyte markers and metabolic genes and enhanced expression of myofibroblast marker genes involved in cytoskeletal organization, accompanied by the formation of actin filament structures within the cell. PPARγ binding was globally reduced in adipocytes after HFD feeding, and Rosi restored the molecular and cellular phenotypes of adipocytes associated with HFD feeding. We identified the TGFβ1 effector protein SMAD to be enriched at HFD-induced promoters and enhancers and associated with myofibroblast signature genes. TGFβ1 treatment of mature 3T3-L1 adipocytes induced gene expression and cellular changes similar to those seen after HFD in vivo, and knockdown of Smad3 blunted the effects of TGFβ1. Conclusions: Our data demonstrate that adipocytes fail to maintain cellular identity after HFD feeding, acquiring characteristics of a myofibroblast-like cell type through reduced PPARγ activity and elevated TGFβ-SMAD signaling. This cellular identity crisis may be a fundamental mechanism that drives functional decline of adipose tissues during obesity.